Indian Capital Market Able to Get Faith or Still the Doom Continues...? Understanding the Volatility of the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Why is the Indian stock market falling? Well, this question has been bothering many who have invested in the stock market. The benchmark Sensex has corrected by about 14 from its peak in Nov 10. The sentiment seems to have reversed quite abruptly. Why is this happening?